Intrinsic bioremediation potential of a chronically polluted marine coastal area. Issue 1 (15th October 2015) - Catania, Valentina; Santisi, Santina; Signa, Geraldina; Vizzini, Salvatrice; Mazzola, Antonio; Cappello, Simone; Yakimov, Michail M.; Quatrini, Paola
Graphical abstract: The Priolo Bay map (eastern coast of Sicily, Ionian Sea) with relative levels of total hydrocarbons (HC) in sediment, bacterial diversity (S) and diversity of culturable HC degraders in sediment and water sampled at six stations on two transects. Highlights: A multidisciplinary survey of a chronically polluted bay is presented. The most polluted sediment host higher abundance and diversity of culturable HC degraders. Oleibacter is isolated for the first time in the Mediterranean Sea. Abstract: A microbiological survey of the Priolo Bay (eastern coast of Sicily, Ionian Sea), a chronically polluted marine coastal area, was carried out in order to discern its intrinsic bioremediation potential. Microbiological analysis, 16S rDNA-based DGGE fingerprinting and PLFAs analysis were performed on seawater and sediment samples from six stations on two transects. Higher diversity and variability among stations was detected by DGGE in sediment than in water samples although seawater revealed higher diversity of culturable hydrocarbon-degrading bacteria. The most polluted sediment hosted higher total bacterial diversity and higher abundance and diversity of culturable HC degraders. Alkane- and PAH-degrading bacteria were isolated from all stations and assigned to Alcanivorax, Marinobacter, Thalassospira, Alteromonas and Oleibacter (first isolation from the Mediterranean area). High total microbial diversity associated to a large selection of HC degraders is believed to contribute to natural attenuation of the area, provided that new contaminant contributions are avoided.